Amylin proprotein processing generates progressively more amyloidogenic peptides that initially sample the helical state - Yonemoto, Isaac T; Kroon, Gerard J A; Dyson, H Jane; Balch, William E; Kelly, Jeffery W (Biochemistry (Easton), 2008)
Human amylin, or islet amyloid polypeptide, is a peptide cosecreted with insulin by the beta cells of the pancreatic islets of Langerhans. The 37-residue, C-terminally amidated human amylin peptide derives from a proprotein that undergoes disulfide bond formation in the endoplasmic reticulum and is then subjected to four enzymatic processing events in the immature secretory granule. Human amylin forms both intracellular and extracellular amyloid deposits in the pancreas of most type II diabetic subjects, likely reflecting compromised secretory cell function. In addition, amylin processing intermediates, postulated to initiate intracellular amyloidogenesis, have been reported as components of intracellular amyloid in beta cells. We investigated the amyloidogenicity of amylin and its processing intermediates in vitro. Chaotrope-denatured amylin and amylin processing intermediates were subjected to size exclusion chromatography, affording high concentrations of monomeric peptides. NMR studies reveal that human amylin samples helical conformations. Under conditions mimicking the immature secretory granule (37 degrees C, pH 6), amylin forms amyloid aggregates more rapidly than its processing intermediates, and more rapidly than its reduced counterparts. Our studies also show that the amyloidogenicity of amylin and its processing intermediates is negatively correlated with net charge and charge at the C-terminus. Although our conditions may not precisely reflect those of amyloidogenesis in vivo, the lower amyloidogenicity of the processing intermediates relative to amylin suggests their presence in intracellular amyloid deposits in the increasingly stressed beta cells of diabetic subjects may be a consequence of general defects in protein homeostasis control known to occur in diabetes rather than serving as amyloid initiators.